ON THE ROLE OF ENGINEERING EDUCATION IN THE DEVELOPMENT OF THE ARCTIC - Nikolai I. Sidnyaev (Moscow Polytechnic University, 2016)
Abstract. The article highlights the concept of development of the Arctic region, and particularly management of development in the Arctic. The author shows the fundamental influence of the Arctic project on the development of science, technology, production, education and public consciousness in Russia. The paper discusses a wide range of Arctic research that makes increasing demands on control systems, materials and manufacturing in general. It is noted that in the framework of the Arctic project a new branch of science and technology has emerged and now is rapidly developing, which requires a significant intensification of scientific work and education.